Random river: Trade and rent extraction in imperial China - Marlon Seror (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2020)
This paper exploits changes in the course of the Yellow River in China to isolate exogenous variation in the natural distribution of economic centers across space and over 2,000 years. Using original data on population and taxation from dynastic histories and local gazetteers, I assess the effect of market access on population density and resource extraction. I find that the changes in connectedness have two opposite effects. First, they induce a very large increase in the level and concentration of economic activity in the short run. Second, they trigger a large increase in taxation per capita and an elite flight, which reverse the concentration effect in the longer run.
Keywords: 330; Agglomerationseffekt; Räumliche Verteilung; Steuereinnahmen; Bevölkerungsdichte; Hwangho (Region); China